Bacterial and cytokine mixtures predict the length of gestation and are associated with miRNA expression in the cervix. (January 2017) - Sanders, Alison P; Gennings, Chris; Svensson, Katherine; Motta, Valeria; Mercado-Garcia, Adriana; Solano, Maritsa; Baccarelli, Andrea A; Tellez-Rojo, Martha M; Wright, Robert O; Burris, Heather H
Aim: Bacterial vaginosis may lead to preterm birth through epigenetic programming of the inflammatory response, specifically via miRNA expression.Methods: We quantified bacterial 16S rRNA, cytokine mRNA and 800 miRNA from cervical swabs obtained from 80 women at 16–19 weeks' gestation. We generated bacterial and cytokine indices using weighted quantile sum regression and examined associations with miRNA and gestational age at delivery.Results & discussion: Each decile of the bacterial and cytokine indices was associated with shorter gestations (p < 0.005). The bacterial index was associated with miR-494, 371a, 4286, 185, 320e, 888 and 23a (p < 0.05). miR-494 remained significant after false discovery rate correction (q < 0.1). The cytokine index was associated with 27 miRNAs (p < 0.05; q < 0.01).Conclusion: Future investigation into the role of bacterial vaginosis- and inflammation-associated miRNA and preterm birth is warranted.